Dinâmica do crescimento e utilização de gramíneas nativas do Rio Grande do Sul submetidas a dois intervalos de descanso entre pastoreios - Seibert, Liane (2019)
This study has the objective to evaluate dynamic of growth and utilization of native grass species Andropogon lateralis, Aristida laevis, Axonopus affinis and Paspalum notatum in a natural pasture of the Central Depression of Rio Grande do Sul submitted to a rotational grazing. The evaluation period was from October 2015 to March 2016. The experimental design was a randomized blocks, with two treatments and three repetitions, with repeated measurements in time. The treatments consisted of two different time intervals between grazing selected by thermal sums of 375 degrees day (DD) and 750 days (DD), considering the leaf expansion of prostrate and cespitose species, respectively. The blocking factor was the proportion of top, slope and lowland reliefs in each repetition. The dynamics of growth and senescence were evaluated, as well as intensity and frequency of defoliation on these grasses. From the evaluated grasses P.notatum was the only that presented differences among seasons for phyllochron, leaf lifespan, duration of leaf elongation and leaf elongation rate, and the highest values were on summer. The species A. affinis was the only one that presented difference between the treatments, and only for leaf elongation rate, which was higher in the treatment of 750 DD.